Om den goda badplatsen : beskrivning och analys över fem skånska badplatsers historia, nyttjande och gestaltning i kontexten av badkulturens allmänna utveckling i Skåne - Lundgren, Cecilia (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The European history of bath has its roots in the Greek culture about 2500 years ago. In every Greek town was situated at least one center of culture, a gymnasium, that contained bath establishements, areas for physical training, restaurants, librarys and readingrooms. Already 400 B.C. Hippokrates, founder of the art of healing, spoke for the waters important qualities in medical treatements.